Identification of the site of interruption in relaxed circles producing during bacteriophage lambda DNA circle replication. - Reuben, R C (1977)
The DNA that accumulates in the lambda infection restricted to the early (circular) stage of replication consists of approximately two-thirds covalently closed circles and one-third relaxed circles bearing a single interruption in either strand of the duplex. The latter molecules are presumed to be a unique class in that the interruption is not repairable by DNA polymerase and ligase. Preferential radioisotopic labeling of the region immediately adjacent to the interruption, followed by hybridization to sheared fragments of the lambda chromosome with varying guanine plus cytosine content, suggested that the nick resides at the position of the mature molecular ends of the lambda chromosome. Digestion of the labeled molecules with restriction enzymes and reconstruction experiments in which Hershey circles were generated by annealing of interrupted strands isolated from the relaxed circles support this interpretation. The results indicate that the relaxed circles consist of a population containing one interruption in either of the two strands of the duplex jointly representing the two "nicks" contained in Hershey circles (in which the cohesive ends are annealed). These molecules could result from the inability of the maturation function to make the required staggered endonucleolytic cuts when the DNA substrate is a monomeric circle rather than a multimeric linear molecule. Alternatively, this interruption could be the result of an endonucleolytic cutting event critical to DNA replication.